Shelf life estimation of Saraswata ghrita - A preliminary evaluation - Robin Badal; Shreshtha Kaushik; Pramod Yadav; Pradeep Kumar Prajapati (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Saraswata ghrita (SG), a multicomponent ayurvedic formulation is well-known for its cognitive properties. Although it is a very effective classical formulation, there is no appropriate data available on its stability study till date. The shelf life of certain Ayurvedic medications is specified in official Gazette, Government of India. However, it is necessary to revalidate the shelf life of each formulation following parameters prevalent in concerned scenario. Hence, an attempt has been made to determine the shelf life of SG through accelerated stability study. OBJECTIVES: The objective is to evaluate shelf life of SG. MATERIALS AND METHODS: SG was manufactured in a pharmaceutical laboratory, All India Institute of Ayurveda, New Delhi following classical reference. The samples were subjected to an accelerated stability study maintaining temperature and humidity 40°C ± 2°C and 75 ± 5% respectively. Relevant analytical parameters were performed at an interval of 0, 1, 3, and 6 months to check the degradation levels in the formulation. RESULTS: Insignificant changes were observed in physicochemical constants and chromatographic assay at different stages of analysis. The product was free from microbial contamination and heavy metals were within the prescribed limits. On extrapolation of the observations, the shelf life of SG is found to be 1 year and 5 months. CONCLUSION: The shelf life of SG corresponds to the classical standards for oleaginous preparations. However, it is less than the specifications set in the official gazette, Govt. of India. This decreased shelf life may be due to milk and salt component present in its composition which possibly speeds up the process of degradation, shortening its shelf life.